Strategi Guru untuk Menanamkan Nilai Kejujuran pada Anak Usia 4-5 Tahun di Kelas A TK Al-Adabiy Kota Pontianak - Adinda Nur Fadilla; Aunurrahman Aunurrahman; Halida Halida (Journal on Education, 2024)
This research aims to describe teachers' strategies for instilling the value of honesty in children aged 4-5 years in class a at Al-Adabiy Kindergarten, Pontianak City. This research uses a descriptive method in the form of qualitative research. This research focuses on teachers' strategies for instilling the value of honesty in children, including teacher strategies in planning and implementing learning to instill the value of honesty, as well as the encouraging and inhibiting factors for teachers in instilling the value of honesty in children. The data obtained in this research was collected from observations, interviews and documentation. The results of this research show that the planning carried out is that the teacher prepares a learning plan which includes activities that can develop the value of honesty and prepares media that can support the values ​​of honesty according to the learning objectives to be achieved. At the implementation stage, teachers apply the values ​​of honesty through learning activities and use exemplary methods and methods of giving advice. The supporting factor for teachers in instilling the value of honesty in children is awareness of the importance of honesty. The inhibiting factor for instilling the value of honesty is the lack of sufficient and effective training to teach and instill the value of honesty.